Biosorpsi Bogenvil (Bougainvillea spectabilis Wild) Terhadap Emisi Timbal (Pb) Pada Kendaraan Bermotor - Nurhikmah, Andi; HS, Syamsidar; Ramadani, Kurnia (Al-Kimia, 2015)
The motorized vehicle activities could result air pollution. One of the pollutan emitted from fuel process is lead which might be reduced by using Bogenvil plants (Bougainvillea spectabilis Wild). Bogenvil were planted in a 1 x 1,5 meter square sized green house where there is a particular hole to flow exhaust fume of motorized vehicle for an hour in each 3, 6, 9 and 12 day after the first exposure. The result shows that Bogenvil leaves have ability to absorb Pb metal emitted from vehicle in response to the exposure time. The highest accumulation of Pb in the leave is 0,469 mg/Kg with exposure time of 12 days. For this reason, the Bogenvil plant can be used as bio- accumulator of timbale metal in the air.